BULLYING IN ENGLISH CLASSES: THOUGHTS HOW TO EDUCATE STUDENTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
I'll discuss my knowledge and thoughts on school bullying in this article. Additionally, I plan to expound on the techniques to make sense of this peculiarity for students all together they don't get mentally and actually get injured from harassing. I trust this will be useful asset for educators and understudies as this peculiarity has extended in all means all things considered schools and other instructive establishments.